Associated Injuries Related to Patients With Facial Fractures. Issue 1 (March 2023) - Ghosh, Rajarshi; Gopalkrishnan, Kulandaswamy
Study Design: Retrospective Study. Objective: To find out the incidence, type, and severity of injuries in other parts of the body in patients diagnosed with facial fractures. The study also analyzed any correlation between these injuries and facial fractures. Methods: A retrospective study of 991 patients with facial fractures during the period of 2006-2016. Results: 111 patients reported associated injuries (11.1%). The most common type of injury was limb injury (33.33%), followed by head injury (22.5%), clavicle fracture (14.7%), rib fracture (10.9%), cervical spine injury (5.4%), and other injuries constituted (13.2%). Multiple associated injuries were observed in 14% of patients. Conclusion: The findings show that facial fracture management is a multidisciplinary approach. Prompt diagnosis and proper management are important to reduce the mortality rate and improve the prognosis of the patient.